The Intellectual Structure of Esports Research - Vallverdu-Jordan, Víctor; Plaza-Navas, Miquel-Angel; Raya, Josep Maria; Torres-Pruñonosa, Jose (Entertainment Computing, 2023)
We aim to map the intellectual structure of eSports research in social Science to understand its evolution and status. This article uses a cocitation analysis focused on eSports scientific literature, which identifies the main clusters, intellectual turning points, and burst papers, showing research priorities, trends, connections and dissemination paths in this research field. This methodology allows us to examine the dominant theories and expands the scientific knowledge of eSports, detecting the main research areas and sources of knowledge. The results show 1) how sportification can be the key to achieving the desired fit between traditional sport and eSports; 2) the existence of eleven different research areas that analyse eSports; and 3) the emerging research topics in this field linked to management, audiences and fan engagement, which are vital issues to be addressed by academia, such as the proposed research agenda outlines.
Keywords: eSports; intellectual structure; bibliometric; trends; cocitation; burst papers